Implementation of contextual approach as meaningful mathematics learning - Rahmita Yuliana Gazali; Muh. Fajaruddin Atsnan (Rafandha Press, 2022)
This study aims to describe the implementation of meaningful mathematics learning with contextual approach and to know the student's response to meaningful mathematics learning. The subjects of this study are students of class VIII B SMP Negeri 7 Banjarmasin as many as 27 people and students of class VIII F SMP Negeri 24 Banjarmasin 2020/2021 lesson year as many as 30 people. Technique of collecting data with observation of learning implementation with contextual approach and questionnaire of student response to learning math meaningful with contextual approach, and documentation. Data analysis technique using percentage. The results show that the implementation of meaningful mathematics learning will take place as planned, containing seven components in a contextual approach, if the teacher is able to translate the essence of each step in a syntactic contextual approach with the media and learning resources. Student's response to the learning of mathematics is significant with the contextual approach of qualification both good and very good, although percentage, student response in class VIII B SMP Negeri Banjarmasin better than student response in class VIII F SMP Negeri Banjarmasin